The The Impact of Task Management, Social Support and Income on Work-Life Balance among Gig Workers - Mohd Yusof, Noorlailahusna; Ismail, Nur Hilmi; Abdul Rashid, Abdul Rashidi; Khan, Hafizah Hammad Ahmad; Mohd Yusof, Muhammad Arif Solehin (Information Management and Business Review, 2024)
The study addresses the growing concern about work-life balance among gig workers in Malaysia, a population facing unique challenges due to the nature of gig employment. This issue is particularly critical as gig workers often struggle with task management, securing social support, and dealing with income volatility, all of which impact their ability to achieve a balanced work-life dynamic. This study aims to analyze the effects of task management, social support, and income stability on the work-life balance of gig workers in Malaysia. A quantitative research methodology was employed, involving a survey of 70 gig workers across various sectors in Kedah. The data was analyzed using correlation analysis to assess the relationships between the independent variables, task management, social support, and income stability, and the dependent variable, work-life balance. The findings reveal that task management, social support, and income stability are all significantly correlated with better work-life balance, with task management being the most influential factor. The implications of this study suggest that improving task management practices, enhancing social support systems, and stabilizing income are crucial strategies for gig platforms and policymakers to consider. These measures can significantly improve the well-being of gig workers and contribute to a more sustainable gig economy. The study also highlights the need for further research to explore these relationships in different cultural contexts and over time, to better understand their long-term effects.